Stable cycling of high-voltage lithium metal batteries in ether electrolytes - Jiao, Shuhong; Ren, Xiaodi; Cao, Ruiguo; Engelhard, Mark H.; Liu, Yuzi; Hu, Dehong; Mei, Donghai; Zheng, Jianming; Zhao, Wengao; Li, Qiuyan; Liu, Ning; Adams, Brian D.; et al. (Nature energy, 2018)
The key to enabling long-term cycling stability of high-voltage lithium (Li) metal batteries is the development of functional electrolytes that are stable against both Li anodes and high-voltage (above 4 V versus Li/Li + ) cathodes. Due to their limited oxidative stability ( <4 V), ethers have so far been excluded from being used in high-voltage batteries, in spite of their superior reductive stability against Li metal compared to conventional carbonate electrolytes. Here, we design a concentrated dual-salt/ether electrolyte that induces the formation of stable interfacial layers on both a high-voltage LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathode and the Li metal anode, thus realizing a capacity retention of >90% over 300 cycles and ~80% over 500 cycles with a charge cut-off voltage of 4.3 V. This study offers a promising approach to enable ether-based electrolytes for high-voltage Li metal battery applications. Ether-based electrolytes offer many advantages compared to other electrolyte systems, but they are not stable in Li metal batteries when operating at high voltages. Here, the authors develop a concentrated ether electrolyte that enables long-term cycling stability of high-voltage Li metal batteries.